Pengujian Prestasi Pembangkit Listrik Tenaga Piko Hidro (PLTPH) Jenis Kincir Air Tipe Overshot Menggunakan Saluran Irigasi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Water energy is a natural resource that is owned by the Indonesian state and electricity is an essential requirement for human life. Water Energy is an alternative energy that can be converted into electrical energy and pollution-free in order to meet community needs. One type of renewable energy is a small-scale hydropower is often called Power pikohidro (PLTPH). In this study include the design of pico hydro power plant types overshot waterwheel types by utilizing the water resources contained in the irrigation area around the reservoir University of Riau. The design is based on the water flow of 0.02 m3/s and water level of 0.4 m.,based on design method was produced the diameter of waterwheel, the number and size of the blades as well as the sizes of penstock. The outside diameter and inside of wheel were 0.6 m and 0,5 m . number of blades were 18 pieces with an area of 0,01 m2, penstock sized of 0.01 m wide and 0.01 m, shaft have 19 mm of the diameter, and 1:4 the ratio of the transmission system. Variations discharge 0,005 m3/s, 0.0056 m3/s, 0.0059 m3/s, 0.0065 m3/s. Maximum power output was generated by the waterwheel of 17,68 Watt and efficiency of 38.84%.Keywords: PLTPH, Design Waterwheel overshot, Efficiency